SEASONALITY OF THE BARK TANNINS CONTENT OF FIVE-YEAR-OLD Acacia mangium TREES GROWN IN NORTHEAST BRAZIL - Souza,Jaltiery Bezerra de (2021)
ABSTRACT This study aimed to assess the influence of the seasonality on the bark tannins content of Acacia mangium trees grown in the Northeastern Brazilian Region and the effect of soil preparation on the results. Two experimental plots of 1.0 ha each were submitted to different soil preparation methods, with two different intensities. The experimental design consisted of four treatments, two types of soil preparation and, two different bark collection seasons (end of the rainy and dry seasons). The bark of the trees was collected in each treatment and the contents of condensed tannins were determined. For each experimental treatment, 15 trees were harvested and debarked. Bark material was submitted to extraction with hot water, obtaining the total solids content (TSC), Stiasny index (I), and the condensed tannins content (CTC). There was no influence of the soil preparation method on the TSC, I, and CTC. However, there was a significant difference in these parameters for tree bark collected in the rainy season, with higher values. The less intensive soil preparation method is recommended due to its lower cost, and bark should be collected at the end of the rainy season for the best yield of condensed tannins.